The Use of Genially-Based Web Learning Media in Enhancing High School Students' Understanding of Payment System and Tools Concepts - Rini Sabrina; Yayat Ruhiyat; Cucu Atikah (AL-ISHLAH: Jurnal Pendidikan, 2025)
The rapid digital transformation in education demands interactive and contextual learning strategies. In economics education, concepts such as payment systems and tools are often abstract and disconnected from students’ real-life experiences. This study investigates the effectiveness of Genially-based web learning media in improving students’ conceptual understanding of these topics. A quasi-experimental design with a pretest-posttest control group was employed involving 36 tenth-grade students from SMAN 2 Krakatau Steel Cilegon. Students were randomly assigned to an experimental group (using Genially media) and a control group (conventional learning). Data were collected through concept tests, questionnaires, and interviews, and analyzed using paired and independent sample t-tests alongside descriptive qualitative analysis. The experimental group showed a significantly greater improvement in posttest scores (gain of 24.89 points) compared to the control group (gain of 14.17 points). Statistical analysis confirmed the difference was significant (p 0.05). Students reported high satisfaction with Genially’s visual appeal, ease of navigation, and relevance to real-world applications. Interview results indicated that the media helped students visualize and better retain abstract economic concepts. The findings demonstrate that Genially-based media effectively enhances conceptual understanding and learning engagement. Its multimedia features support cognitive processing and align with constructivist and multimedia learning theories. This suggests that integrating well-designed web-based tools can significantly improve economics education at the high school level.